Does a Student's Personality Influence Global Attentiveness and Internationalism in an International Business Course?. Issue 4 (1st October 2016) - Chen, Jiun-Shiu; Stevens, Jeffery; Cox, Susie S.; Tudor, Thomas R.
ABSTRACT: Learning outcomes for international business (IB) courses are designed to do more than simply impart IB knowledge. However, past studies have had mixed results on the impact of learning in IB courses. This study examines whether a student's personality may affect learning outcomes. The results suggest that after completing an IB course, students become more interested in keeping up with important international issues (i.e., global attentiveness) and also benefit from a stronger global outlook (i.e., internationalism). The Big Five personality trait, openness to experience, partially affected these learning outcomes. Students in our study with a high degree of openness to experience were the most global attentive before and after taking the IB course. However, openness to experience levels did not significantly influence levels of internationalism. Implications of this study and suggestions for future research are also discussed.